KOORDINASI EKSTERNAL DINAS LALU LINTAS DAN ANGKUTAN JALAN TENTANG IMPLEMENTASI SISTEM SATU ARAH DIKOTA BOGOR - Udin, Khoerudin; Hernawan, Denny; Purnamasari, Irma (JURNAL GOVERNANSI, 2017)
In implementing the policy of One Way Direction System in Bogor City, it is necessary to have well-coordination between Traffic and Road Transportation Agency (DLLAJ) of Bogor City with related Institutions/Agencies. If one of the agencies do not perform their duty well, then their goal to overcome the congestion will run ineffectively.The purpose of this study is to know the direction of coordination between traffic and road transportation Bogor City with other agencies in applying a one-way direction system. The theory used in this research is by using the coordination theory of Handyaningrat which states that to produce a coordination can be measured through five variables as follow: (1) Communication, (2) Awareness of the Importance of Coordination, (3) Participant Competencies, (4) Agreements, Commitments, and Coordination Incentives, and (5) Continuity of Planning.The method used is descriptive analysis using Qualitative approach. The data analysis technique used is to use the calculation of Weighted Mean Score (WMS). Technical data used are literature study, field study, interview and questionnaire. Unit of analysis of this study consist of 11 respondents. While the sampling technique used is saturated sample technique.In general, the results of external coordination conducted by Traffic and Road Transportation Agency (DLLAJ) of Bogor City in implementing one-way direction system is obtained an average score of 3.81 which according to structuring criteria are in good category. While the existing variety in moderate criteria is an indicator of whether or not there are casualties for offenders exist with average score of 3.18. Meanwhile the indicator that produces a very good score is on the indicator of whether or not the executor of the activity with a score of 4.18. In sum, the average score of all indicators is in good criteria.Keywords: Coordination, Implementation, Policy.